Left Atrial Strain and the Risk of Atrial Arrhythmias From Extended Ambulatory Cardiac Monitoring: MESA - Matthew P. Huber; Jay A. Pandit; Paul N. Jensen; Kerri L. Wiggins; Ravi B. Patel; Benjamin H. Freed; Alain G. Bertoni; Sanjiv J. Shah; Susan R. Heckbert; James S. Floyd (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Abnormalities in left atrial (LA) function often occur before LA structural changes and clinically identified atrial fibrillation (AF). Little is known about the relationship between LA strain and the risk of subclinical atrial arrhythmias detected from extended ambulatory cardiac monitoring. Methods and Results A total of 1441 participants of MESA (Multi‐Ethnic Study of Atherosclerosis) completed speckle‐tracking echocardiography and cardiac monitoring during 2016 to 2018 (mean age, 73 years); participants in AF during echocardiography or during the entire cardiac monitoring period were excluded. Absolute values of LA reservoir, booster pump, and conduit strains were measured. We evaluated associations of LA strain with monitor‐detected AF, premature atrial contractions, and supraventricular tachycardia. Primary analyses adjusted for demographic variables, blood pressure, diabetes, smoking, and clinical cardiovascular disease. Cardiac monitoring (median, 14 days) detected AF in 3%. Each SD (4.0%) lower (worse) LA booster pump strain was associated with 84% higher risk of monitor‐detected AF (95% CI, 30%–162%), 39% higher premature atrial contraction frequency (95% CI, 27%–53%), and 19% higher supraventricular tachycardia frequency (95% CI, 10%–29%). Additional adjustment for NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), LA volume index, tissue Doppler a′ peak velocity, left ventricular ejection fraction, and global longitudinal strain had little impact on associations. Findings were similar for LA reservoir strain and null for LA conduit strain. Conclusions In a multiethnic community‐based cohort, impaired LA strain was an important correlate of subclinical atrial arrhythmias, even after adjustment for conventional measures of LA structure and function.